Technology-enhanced teaching and learning: a case of the faculty of Art in Kwame Nkrumah University of Science and Technology - Annku, Epilogue (2015)
A thesis submitted to the Department of General Art Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of